The Implementation of Problem Based Learning Integrated with STEM-Based Worksheets to Improve Learning Motivation - Hasanah, Zainatul; Ritonga, Soleh; Ikhsan, Zainuril; Suarni, Suarni (Asian Journal of Science Education, 2021)
The teaching and learning process in the classroom has not been able to arouse students 'learning motivation so that the learning motivation of students is not maximal, students' learning motivation is not maximized, seen from the learning process there are still students who have not been able to focus their attention and concentration on learning, so that only a few participants students who are active in learning. In addition, there are still many students who are not confident, do not dare to ask questions and when doing group presentations not all students dare to speak, only rely on other friends. The research approach used is quantitative with the type of quasi-experimental research, the research design used is Pretest-Posttest Non-Equivalent Control Group Design. The study population was all students of class 10th Senior High School 1 Peusangan and Senior High School 2 Peusangan, amounting to 252 people. The sampling technique used was purposive sampling, the sample in this study consisted of 140 students. Instruments to measure motivation using a questionnaire in the form of pretest and posttest questions. Data analysis consisted of normality test, homogeneity test, N-gain test, paired sample t-test and independent sample t-test, at a significant level of 0.05. The results showed that there were differences in the learning motivation of students in the experimental class and the control class on environmental pollution material in class 10th Negeri Bireuen district.